SEEDS ANALYSIS OF VEGETABLE BEANS VICIA FABA L., OBTAINED FROM THE SAMPLES WITH UNUSIAL FIELD GERMINATION - I. T. Balashova (Ovoŝi Rossii, 2012)
Preventive measures are most effective methods of plants pathogens control. Broad beans - Vicia faba L. - are infected by Uromyces fabae (Grev.) de Bary ex Fuckel, Ascochyta fabae Speg. and broad bean mottle virus (BBMV) at the Middle part of Russian Federation. Degrees of diseases spread were: for Uromyces fabae (Grev.) de Bary ex Fuckel - 76% (at 2009) and 6,5% (at 2011); for Ascochyta fabae Speg. - 100% (at 2009) and 1,5% (at 2011), for broad bean mottle virus - 23% (at 2009) and 46,3% (at 2011). It is known, that Ascochyta fabae Speg. is spreading by seeds. It has been proved by analysis of broad beans seeds germinated in the humid chamber. The significant negative correlation between the degree of plants affection and the degree of seeds germination has been established (r= -0,49; tr = 3,50>t05 = 2,01). This correlation is significant on 5%-level of significance. Recommendations for treatment of broad bean seeds against Ascochyta fabae Speg have been done for breeders.